Pertanggung Jawaban Negara Terhadap Tindak Pidana Internasional - F, Fatahillah (Jurnal Ilmu Hukum Reusam, 2021)
Limited state responsibility on liability for acts that violate international law, for example refusing the entry of foreign citizen into his territory does not lead to state accountability is an important issue, state responsibility in defined as the bases for carrying out its obligations the meaning of the elements is difficult. Proven because the act of omitting the state apparatus gives rise to a dilemma, in international law practice since the and of the second worid war. Show clearly that individually accountable for the actions carried out when acting as officials in certain positions, ending the community so that each individual is responsible for the international actions he does.